Physiological and biochemical changes in potato under water stress condition - Mahmud, A.A.; Hossain, M.; Kasian, M.S.; Hoque, M.A. (Springer, 2015)
Four CIP potato clones with one check variety Asterix were planted in the 3rd week of November 2011 at horticulture research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University to observe physiological and biochemical changes under water stress. CIP 396244.12 and CIP 393371.58 showed higher membrane stability index (lowest injury) after 10 and 20 days of drought treatment. These two genotypes also accumulated more proline and total soluble sugar in leaves with less destruction in total chlorophyll under water stress condition than control. An increase in chlorophyll a/b ratio was found in CIP 396244.12, followed by CIP 393371.58 under water stress condition. The highest catalase activity was observed in CIP 396244.12, followed by CIP 393371.58 under water stress condition. Our results revealed that CIP 393371.58 and CIP 396244.12 showed greater adaptability in changing environment.